Perceptions of furniture-buying urban Filipinos on traditional wood furniture - Villafuerte, Rowell T.; De Leon, Luna Liezl N. (Quezon City University of the Philippines Diliman, 2024)
The growing accessibility of the furniture market, shifting furniture trends, and the changing living conditions in Metro Manila has affected the perceptions of young urban Filipinos on traditional wood furniture, which has led to the struggle on how traditional wood furniture can continue its relevance in the urban setting. The study aims to learn how urban Filipinos perceive traditional wood furniture, how it has been influenced by personal views and experiences and by different external factors, and its implications on the traditional wood furniture industry. The research employs a narrative qualitative approach, where ten young Filipinos residing in Metro Manila were selected through purposive sampling method. Semi-structured interviews were conducted via face-to-face meetings and online setup depending on the availability of the participants. The data was analyzed with the use of reflexive thematic analysis. Findings showed that participants perceive traditional wood furniture as impractical and inaccessible for modern dwellings due to the cost and effort needed to acquire them. Because of the influences of different external factors, young urban Filipinos prefer to go for popular brands due to familiarity and the bandwagon effect. Accessibility has also become one of the main concerns of the participants, opting for stores that are nearer to their dwellings and accessible on online platforms. These changes in perceptions and the different external factors have negatively affected the performance of traditional wood furniture in the market, as they are unable to reach and connect with a younger customer base in the city. The traditional wood furniture industry must adapt to the changing times to continue its growth or risk losing the market entirely in the future.
In partial fulfillment for the Degree of Bachelor of Science in Interior Design
Thesis
Keywords: Furniture design -- Philippines; Wood furniture; Traditional wood furniture